Developing micro-/nanoparticulate drug delivery systems using “design of experiments” - Singh, Bhupinder; Bhatowa, Rahul; Tripathi, Chandra Bhushan; Kapil, Rishi (International Journal of Pharmaceutical Investigation)
Of late, micro and nanoparticluate drug delivery systems have been gaining immense importance primarily attributed to their improved drug release controlling and targeting efficiencies. Also, the small particle size and desirable surface charge associated with these delivery systems render them suitable for specific applications like lymphatic uptake, pulmonary uptake, tumor targeting, brain targeting, etc. For decades, micro and nanoparticulate systems have been prepared by the conventional “trial and error” approach of changing One Variable at a Time (OVAT). Using this methodology, the solution of a specific problematic formulation characteristic can certainly be achieved, but attainment of the true optimal composition is never guaranteed. Thus, the present manuscript provides an updated account of the systematic approach “Design of Experiments (DoE)” as applicable to formulation development of microparticles and nanostructured systems. Besides providing a bird’s eye view of the various experimental designs and optimization techniques employed for DoE optimization of such systems, the present manuscript also presents a copilation of the major micro/nano-structuctred systems optimized through DoE till date. In a nutshell, the article will act both as a ready reckoner of DoE optimization of micro/nano drug delivery systems and a catalyst in providing an impetus to young pharmaceutical “nano & micro” researchers to venture into the rewarding field of systematic DoE optimization.
Keywords: Contour plots; microparticles; nanoparticles; optimization; response surface